Compatibility of phorate and chlorpyriphos with Trichoderma harzianum (Rifai.) applied for integrated disease management in black pepper (Piper nigrum L.) - Sarma, R Stephen Jebakumar, M Anandaraj, Y R (Journal of Spices and Aromatic Crops, 2000)
The compatibility of the biocontrol agent, Trichoderma harzianum utilized for the management of Phytophthora foot rot of black pepper (Piper nigrum), with phorate and chlorpyriphos applied for the management of nematodes and mealybugs respectively, was studied. The experiments were conducted in vitro and in soil at different concentrations for each chemical considering the recommended dose (6-36’ ppm ai for phorate and 10-40 ppm ai for chlorpyriphos). The, in vitro studies indicated that phorate at 6-36 ppm did not’ affect radial growth and sporulation of T. harzianum, whereas, chlorpyriphos at 10-40 ppm retarded radial growth up to 50% at 24 hand 48 h but not at 72 h, and retarded sporulation. In soil, there was no significant difference in the number of viable colonies of T. harzianum at 1% concentration for phorate concentrations of 1000 and 2000 ppm. However, incorporation of chlorpyriphos into soil resulted in increase in number of viable colonies of T. harzianum. The study indicated that phorate and chlorpyriphos could be safely applied with T. harzianum for the management of Phytophthora foot rot, nematodes and mealybugs on black pepper.